2002
DOI: 10.1021/jf020292i
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Black Currant Anthocyanin Aglycons and Their Glycosides Measured by Chemiluminescence in a Neutral pH Region and in Human Plasma

Abstract: The antioxidant activity of nine anthocyanin glycosides was measured in a neutral pH region using a chemiluminescence (CL) emission system in the presence of an H(2)O(2)-acetaldehyde system, and the intensities were found to be affected by three factors, pH value and both moieties of the aglycon and C-3 sugar. With an increase in pH from 4.0 to 9.0, the CL intensities increased from pH 5.0, reached their maxima at pH 6.0-7.0, and decreased at pH 9.0. Comparison of the intensities among the 3-glucosides with fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 11 publications
2
36
0
2
Order By: Relevance
“…The best fit-adjustment (lower scattering) was found in the samples having less than 100 mg/100 g of fw of total anthocyanins.. This evidence suggested that the measure of chromatic parameters could be a good tool to predict the levels of anthocyanins in storage cherries and predict the beneficial human health effects of each sweet cherry cultivar, since anthocyanins exert antioxidant activity (Lapidot, Harel, Akiri, Granit, & Kanner, 1999;Matsumoto, Nakamura, Hirayama, Yoshiki, & Okubo, 2002;Wang et al, 1999). Therefore, for cherries for human consumption, it seems important to have a simple and non-destructive technique for anthocyanins content determination, and in this way easily and quickly assess and monitor cherry quality on a large number of cherries.…”
Section: Correlations and Regressions Between Anthocyanins Content Anmentioning
confidence: 89%
“…The best fit-adjustment (lower scattering) was found in the samples having less than 100 mg/100 g of fw of total anthocyanins.. This evidence suggested that the measure of chromatic parameters could be a good tool to predict the levels of anthocyanins in storage cherries and predict the beneficial human health effects of each sweet cherry cultivar, since anthocyanins exert antioxidant activity (Lapidot, Harel, Akiri, Granit, & Kanner, 1999;Matsumoto, Nakamura, Hirayama, Yoshiki, & Okubo, 2002;Wang et al, 1999). Therefore, for cherries for human consumption, it seems important to have a simple and non-destructive technique for anthocyanins content determination, and in this way easily and quickly assess and monitor cherry quality on a large number of cherries.…”
Section: Correlations and Regressions Between Anthocyanins Content Anmentioning
confidence: 89%
“…The chemical structure (position, number, and types of substitutions) of the individual anthocyanin molecule also has a bearing on the degree to which anthocyanins exert their bioactive properties [11, 12] and the structure/function relationships also influence the intracellular localization of the pigments [7]. The anthocyanin literature includes some controversy over the relative contributions of glycosylated anthocyanins versus aglycones in terms of bioavailability and bioactive potential [7, 13, 14, 15, 16]. Originally, it was assumed that only aglycones could enter the circulation circuit, however, absorption and metabolism of anthocyanin glycosides has now been demonstrated.…”
Section: Anthocyanins and Biomedicinal Propertiesmentioning
confidence: 99%
“…This is partly due to their anti-inflammatory properties (González-Gallego et al 2010;Landberg et al 2011;Rotelli et al 2003), antioxidant and free radical scavenging activities (García-Alonso et al 2009;Gray and DeWitt 1999;Kahkonen and Heinonen 2003;Matsumoto et al 2002;Tsuda et al 1994;Wang et al 1997), peroxidation inhibition (Tsuda et al 1996), and estrogenic/anti-estrogenic activity (Cassidy et al 2003). It has been largely proven that the beneficial potential of polyphenols as part of a healthy diet cannot be only explained by their antioxidant characteristics (Virgili and Marino 2008).…”
Section: Introductionmentioning
confidence: 99%